Eco design : Manual for ecological design - Yeang, Ken (UK John Wiley & Sons, 2006)
You'll find clear instructions on how to design, build and use a green sustainable architecture in Ecodesign. Author Ken Yeang will show you how to produce and maintain ecosystem-like structures and systems whose content and outputs not only integrate benignly with the natural environment, but whose built form and systems function with sensitivity to the locality's ecology as well in relation to global biospheric processes. He will help you learn to develop structures and systems that are low consumers of non-renewable resources, built with materials that have low ecological consequences and are designed to facilitate disassembly, continuous reuse and recycling, and that at the end of their useful lives can be reintegrated seamlessly back into the natural environment. Each of these aspects, and other attendant ones, is examined in detail with regards to how they influence design and planning.
Keywords: ARCHITECTURE AND ENVIRONMENT (AR-ENV)